(untitled) (Sains Humanika, 2015)
The purpose of this study is to determine relationship between organizational antecedent and knowledge sharing practices among academician at Malaysia Research Universities. The hypothesis for this research are organizational antecedent has relationship with knowledge sharing practices. The variables in this study are organizational antecedent which consist of people, organization and technology, well for knowledge sharing practices consist of socialization, externalization, combination and internalization. Applying the theory of multiple perseptive for organizational antecedent and SECI for knowledge sharing practices. The data analysis measured this research were using software of statistical package for social science (SPSS) version 22 and measuring for structural equation modelling (SEM) software of analysis of moment structures (AMOS) version 22. The findings of this study largely support the hypothesized relationship proposed in the theoretical model. Specifically, the results the relationship of organizational antecedents and knowledge sharing practice. This research make several theoretical contributions and provides further insight on knowledge sharing practice among academician in research universities. Methodological and practical implications were discussed. This research helped to produce a segment in a more inclusive global picture of independent variable that organizational antecedents and dependent variable that knowledge sharing practice.